Partial replacement of silica nanoparticles in cement paste for CO2 regeneration capture application - Mahmud, Mudrikah Sofia; Mohd Daud, Farah Diana; Sarifuddin, Norshahida; Mohd Zaki, Hafizah Hanim; Nordin, Norhuda Hidayah; Mohammad, Nur Farahiyah (IIUM Press, 2024)
A promising, supplementary material, highly reactive silica nanoparticles tend to react with calcium species (Ca2+) in cement, which produces more hydrated phases. The high amount of calcium species and the potential of capturing carbon dioxide (CO2) through carbonation implies the suitability of cement paste as a CO2 sorbent material. However, limited studies could be found highlighting the effect of silica nanoparticle inclusion on the CO2 capture property of hardened cement paste. Thus, this study investigates the effect of silica nanoparticle partial replacement on the CO2 capture capacity and regeneration performance of hardened cement paste. XRD and SEM analysis proved the formation of more hydrated phases upon partially replacing silica nanoparticles in cement. Partial replacement of 3.00 % with silica nanoparticles significantly improved CO2 regeneration capture at room temperature among the other cement paste samples. This study found that the presence of silica nanoparticles in cement paste triggered the formation of more hydrated phases, which served as active sites for CO2 capture to occur and, thus, improved the CO2 capture capacity and regeneration performance.